The study of employees’ innovative behaviour at industrial enterprises - Tatyana A. Vinogradova; Mikhail S. Kuvshinov (Journal of New Economy, 2022)
Expanding the scale of innovation activity proceeds from companies’ intense interest in retaining and strengthening their market positions. The success of this activity considerably depends on the employees’ competencies in creating and introducing innovations. The paper aims to test the method for assessing the level of employees’ innovative behaviour (LEIB) at industrial enterprises. The tenets of personnel and innovation management constitute the methodological basis of the research. The LEIB is determined using the own developed method, which implies the calculation of the composite indicator based on 40 indicators that characterise the innovative behaviour of employees at individual and company levels. Empirical evidence is the data on innovative development of OOO Modern Glass including accounting and management reporting, business plans, forecasts. The tested method proved to be practically sound: the analysis revealed a low level of employees’ innovative behaviour. To adjust the company policy on innovation management, the paper suggests a set of measures including the refinement of the remuneration system; development of the competencies in the field of innovative development; organisation of events to increase awareness about the company’s innovation activity. The forecasts estimate that these measures are to increase the level of employees’ innovative behaviour by 16 %.